2023
DOI: 10.3390/ijms24021646
|View full text |Cite
|
Sign up to set email alerts
|

Recent Pharmacological Options in Type 2 Diabetes and Synergic Mechanism in Cardiovascular Disease

Abstract: Diabetes Mellitus is a multifactorial disease with a critical impact worldwide. During prediabetes, the presence of various inflammatory cytokines and oxidative stress will lead to the pathogenesis of type 2 diabetes. Furthermore, insulin resistance and chronic hyperglycemia will lead to micro- and macrovascular complications (cardiovascular disease, heart failure, hypertension, chronic kidney disease, and atherosclerosis). The development through the years of pharmacological options allowed us to reduce the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 115 publications
0
22
0
Order By: Relevance
“…( Andreadi et al, 2022 ).This process results in the production of advanced glycosylated end products (AGEs) or activation of the polyol pathway, which bind to receptors and induce the expression of adhesion molecules, impairing endothelial function and elevating the risk of cardiovascular disease. ( Nakamura et al, 1993 ; Schmidt et al, 1995 ; Andreadi et al, 2023 ). The overproduction of reactive oxidative species (ROS) and reactive nitrogen species (RNS), or an imbalance between ROS and cellular antioxidants, contributes to the development of various diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…( Andreadi et al, 2022 ).This process results in the production of advanced glycosylated end products (AGEs) or activation of the polyol pathway, which bind to receptors and induce the expression of adhesion molecules, impairing endothelial function and elevating the risk of cardiovascular disease. ( Nakamura et al, 1993 ; Schmidt et al, 1995 ; Andreadi et al, 2023 ). The overproduction of reactive oxidative species (ROS) and reactive nitrogen species (RNS), or an imbalance between ROS and cellular antioxidants, contributes to the development of various diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperglycemia free fatty acids (FFA), and pancreatic beta cell insulin release directly or indirectly induce the overproduction of ROS, disrupting intracellular homeostasis. ( Andreadi et al, 2023 ). Animal model studies have identified SGLT-2i as a potent antioxidant drug capable of reducing oxidative sress by modulating the production of pro-oxidant enzymes such as Nox, eNOS, and xanthine oxidase.…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia is one of the most critical complications for patients with type 2 diabetes (T2D), which can directly affect prognosis and significantly reduce their quality of life, including the risk of bone fractures and frailty. The amount of people with diabetes has been increasing rapidly, with estimates claiming that by 2045 there will be over 700 million patients worldwide [ 1 ]. People with T2D are known to suffer from insulin resistance, inflammation, AGE accumulation, and oxidative stress that affect muscle mass and strength, systemic metabolism, and mitochondrial dysfunction, resulting in sarcopenia [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that even patients with type 1 diabetes can develop sarcopenia as a long-term complication [ 5 ]. Additionally, in recent years, large-scale clinical trials have reported the usefulness of SGLT2 for cardiovascular disease, and the guidelines recommend the drugs for diabetes, but some reports suggest the possibility of the progression of sarcopenia or loss of muscle mass, based on the mechanism of pharmacological effects [ 1 ]. Preventing sarcopenia is crucial, especially for east Asian patients with diabetes, who often have less muscle mass than Western people.…”
Section: Introductionmentioning
confidence: 99%
“…A complete picture of pathophysiological mechanisms in patients affected by type 2 diabetes mellitus is reported in detail in the review of Andreadi et al [2]. The authors highlight the relevant role of inflammatory cytokines and oxidative stress, which, in the pre-diabetic phase, could favor the onset of type 2 diabetes mellitus.…”
mentioning
confidence: 99%